INVESTMENT FEASIBILITY COMPARATIVE ANALYSIS OF GREEN BUILDING AND CONVENTIONAL IN DKI JAKARTA - Yasmin Ramadian; Oei Fuk Jin (Jurnal Infrastruktur, 2024)
Sustainable buildings generally demonstrate a friendly environment, save energy and reduce operational costs, thus opening up significant investment opportunities in green buildings of the office property type. It is a shame that currently there are still very few office building developers who apply the green building concept, meanwhile the green building concept provides 31% greater profits than conventional buildings. This study aims to analyze the financial feasibility of four office buildings which are divided into two categories, namely category one (building 1 and Building 3) with a grade A building type and category two (building 2 and building 4) with a grade B building type. Building 1 and building 2 has received green building certification issued by GBCI. Building 2 and building 4 are buildings with a conventional concept. Calculation analysis is carried out using the Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PP) methods. Based on the results of the analysis, from the two categories of building types, the results showed that the NPV of each building was said to be financially feasible with an NPV ratio of 294% (category 1) and 162% (category 2). The IRR obtained exceeds the MARR value, with a comparison of 54% (category 1) and 21% (category 2). The payback period is less than the project investment period, namely 20 years, with a difference of 5 years (category 1) and 3 years (category 2). The office buildings with the highest and best NPV are Building 1 and Building 3 (category 1), so that even though the construction costs and green building design planning costs incurred are higher, in the research object of each building there are quite significant differences in NPV and IRR and It is hoped that all new construction and renovation work carried out by developers can apply the green building concept.